Nghiên cứu khả năng chống ăn mòn của nanocompozit poly(anilin-Co-O-toluidin)/-Fe2O3 - An, Trần Văn; Quế, Lê Xuân; Vỹ, Uông Văn (Vietnam Journal of Chemistry, 2016)
Poly(aniline-co-o-toluidine) (PAT)/Fe2O3 (PATF) nanocomposite were synthesized by electrochemical methods on 316L stainless steel electrode. Aniline (ANi) and o-toluidine (o-Tol) were dissolved in 0.5 M H2SO4 and α-Fe2O3 with different mass ratios were added in the solution. The solution was stirred by speed of 200 rpm during the process. The obtained nanocomposite material were washed by double distilled water to pH = 7, dried and then pulverized. The composite were dissolved in N,N-dimethylformamide (DMF) in 24 hours. The DMF containing nanocomposite was coated on CT3 carbon steel electrodes, the electrodes were dried from 70 to 80 oC for 24 h. Anticorrosion properties of the coating were measured by electrochemical techniques in 3 % NaCl solution at room temperature, were shown by potential corrosion (Ecor), corrosion current (Icorr) and polarization resistance (Rp) parameters. Keywords. Corrosion, nanocomposite, poly(aniline-co-o-toluidine), electrochemical, Fe2O3